The Influence Of JASA TAMI (Healthy Adolescents Without Anemia) Booklet Media On Adolescent Girls In Islamic Boarding Schools Mizanul ‘Ulum Sanrobone In 2023 - M, Fifiana Agustianingsih; Rahma, Nur Rahmawati Sholihah; Rahayu, Budi (Fakultas Kebidanan Institut Kesehatan Medistra Lubuk Pakam, 2024)
Background: Anemia is a health problem that often occurs in adolescent girls. Anemia is a condition in which the number and size of erythrocytes or hemoglobin concentration is below the threshold value and results in a decrease in the overall blood transport capacity of the body. The prevalence of adolescent anemia ranges from 40-80%. According to WHO, the incidence of anemia in adolescent girls in developing countries is about 53.7% of all adolescent girls. Objective: To determine the influence of the JASA TAMI (Healthy Adolescents Without Anemia) booklet media on the knowledge and attitudes of anemia prevention for adolescent girls at the Mizanul 'Ulum Sanrobone Islamic Boarding School in 2023. Method: The researcher used pre-experiment method with one group pretest-posttest design. The research time is on May 22-May 27, 2023 with 32 respondents. The sampling technique used total sampling. All respondents were given Jasa Tami's booklet media